Controversies in orbital reconstruction—II. Timing of post-traumatic orbital reconstruction: A systematic review. Issue 4 (April 2015) - Dubois, L.; Steenen, S.A.; Gooris, P.J.J.; Mourits, M.P.; Becking, A.G.
Abstract The timing of orbital reconstruction is a determinative factor with respect to the incidence of potential postoperative orbital complications. In orbital trauma surgery, a general distinction is made between immediate (within hours), early (within 2 weeks), and late surgical intervention. There is a strong consensus on the indications for immediate repair, but clinicians face challenges in identifying patients with minimal defects who may actually benefit from delayed surgical treatment. Moreover, controversies exist regarding the risk of late surgery-related orbital fibrosis, since traumatic ocular motility disorders sometimes recover spontaneously and therefore do not necessarily require surgery. In this study, all currently available evidence on timing as an independent variable in orbital fracture reduction outcomes for paediatric and adult patients was systematically reviewed. Current evidence supports guidelines for immediate repair but is insufficient to support guidelines on the best timing for non-immediate orbital reconstruction.